Developing waqf land computing: a preliminary study on the used of web-based applications and spatial database / Siti Nurbaya Ismail ... [et al.] - Ismail, Siti Nurbaya; Idrus, Zanariah; Abdul Razak, Nor Hafizah (2015)
Around the world, the most commonly properties that being waqf, is land as its’ use can be extend of, and making the benefit of waqf grows bigger to its beneficiary. However to what extent does the efficiency of waqf land data management currently being practice? This paper will discuss on the preliminary study done to identify the problems occur in managing waqf land data, thus, inspiring the development of waqf land computing by proposing web-based GIS model. The first objective of this research is, to investigate current practice of waqf land data management. Second objective is to investigate the used of web-based applications and spatial database in waqf land data management. Based on the findings, the third objective is to develop a web-based GIS model. Comparative study is done by investigating the current practice of Malaysia’s waqf land data management. Study towards web-based applications and spatial database also had been conduct. Web-based applications had been used over the manual system for it most significant reason which is; its capability to store data on the servers that reflects the management of record keeping process. Where by spatial databases is one of the core foundations of any GIS program, the storage systems containing all of the data that is necessary for a finalized and fully functional GIS map to display all of the data layers that were included in its design. The preliminary result of the study shows that the integration between web-based applications and spatial database in waqf land data management brings tremendous new opportunity, making record keeping process more systematic, effective and efficient.